Analisis Semiotika terhadap Penggunaan Emoji dalam Komunikasi Daring oleh Remaja - Yuliana Khoirun Nisa (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to describe the meaning of emoji use in online communication by adolescents using a semiotic approach. Emojis, as visual symbols on social media, have become increasingly popular representations of emotions and expressions, especially among adolescents. Within a semiotic framework, signs such as emojis not only represent literal meanings but also imply contextual meanings that can be interpreted in various ways. This study used a descriptive qualitative approach with data collection techniques including observation and in-depth interviews. The subjects were adolescents aged 15 to 19 in an urban environment. The results indicate that emojis are used as a reinforcement of emotional expression, a tool for marking group identity, and as a symbolic part of social interaction. These findings suggest that understanding the meaning of emojis is strongly influenced by the communication context, relationships between speakers, and the evolving digital culture.